The relationship between working alliance and client outcomes in coaching: A meta-analysis - Graßmann, Carolin; Schölmerich, Franziska; Schermuly, Carsten C (Human relations (New York), 2020)
A growing number of studies emphasize the working alliance between the client and the coach to be a key factor in coaching. Synthesizing 27 samples (N = 3563 coaching processes), this meta-analysis sheds light on the relationship between working alliance and a broad range of coaching outcomes for clients. The meta-analytic results indicate a moderate and consistent overall relationship between a high-quality working alliance and coaching outcomes for clients (r = .41, 95% CI [.34, .48], p < .001). Working alliance was positively related to all desirable coaching outcomes (range: r = .32 to .64), with the strongest relationship to affective and cognitive coaching outcomes. Moreover, working alliance was negatively related to unintended negative effects of coaching (r = –.29). Results revealed no differences regarding the type of clients, coaches’ expertise, number of coaching sessions, and clients’ or coaches’ perspectives. Similar to other helping relationships like psychotherapy or mentoring, the results support the importance of a high-quality working alliance in coaching.